الشمول المالي في الدول العربية -الإمارات العربية المتحدة نموذجا- (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخص:تهدف هذه الورقة البحثية لتسليط الضوء على تجربة البلدان العربية في تطبيق الشمول المالي مع التركيز على نموذج الامارات العربية المتحدة باعتبارها رائدة في هذا المجال. وتم الاستعانة بالمنهج الوصفي التحليلي ومنهج دراسة حالة للخروج بجملة من الاستنتاجات من أهمها التباين الحاصل في تجسيد الشمول المالي على مستوى البلدان العربية، أما فيما يخص الإمارات العربية المتحدة فقد وفر نظامها المصرفي بمختلف مستوياته، البنية التحتية الرقمية التي وسعت من الخدمات المالية الرقمية بمختلف أشكالها مما انعكس إيجابا على الشمول المالي فيها ورفع من مستواه. في حين يمكن اقتراح تعميق العمل باتجاه تقليص الفجوات بين الجنسين والمناطق وخلق منتجات مالية رقمية متوافقة مع متطلبات النساء والبالغين الفقراء والمقيمين في المناطق النائية.الكلمات المفتاحية: شمول مالي، مؤشر شمول مالي، خدمات مالية رقمية. Abstract:   This research paper aims to highlight the experience of the Arab countries in applying the financial inclusion, focusing on the model of the United Arab Emirates as a pioneer in this field. The descriptive analytical methodology and a case study method were used to come up with a set of conclusions, the most important of which are the variation in embodying the financial inclusion at the Arab countries level as for the United Arab Emirates, it has provided its banking system at all its various levels the digital infrastructure that expanded the digital financial services in its various forms, which has positively affected the financial inclusion and raised its level. While it is possible to propose to deepen the work towards reducing the gender and the regional gaps as well as creating digital financial products compatible with the women requirements, the poor adults and the residents of the remote areas. The Keywords: The financial inclusion, the financial inclusion index, the digital financial services, the Arab countries, the United Arab Emirates.